Post-merger Restructuring of the Labor Force - Britta Gehrke; Ernst Maug; Stefan Obernberger; Christoph Schneider (Institute of Labor Economics (IZA), 2021)
We study the restructuring of the labor force after mergers and acquisitions. Overall restructuring is large. Net employment of targets declines by more than half within two years after acquisitions relative to a matched sample, and is concentrated in targets that close all establishments. There is a substantial increase in employee turnover. We place our analysis within a framework in which acquirers seek growth options from targets and provide managerial capabilities to organize production more efficiently. Consistent with this framework, we show that growth and turnover are both higher for managers, and that firms become more hierarchical if they grow and if they become more diversified. Acquirers have a better-educated, better-paid, and more qualified workforce than targets, and they adapt the workforce by hiring new employees who are much younger and less expensive. Mergers create internal labor markets, which are more active if firms have more managerial capacities. However, most hiring is external, especially for managers.
Keywords: G30; G34; J24; J31; M51; 330; M&A; restructuring; employment; internal labor markets